1970
DOI: 10.3329/sjps.v3i1.6798
|View full text |Cite
|
Sign up to set email alerts
|

RP-HPLC Method for Simultaneous Estimation of Amlodipine Besylate and Hydrochlorothiazide in Combined Dosage Forms

Abstract: A reverse phase high performance liquid chromatographic (RP-HPLC) method has been developed for the simultaneous estimation of Amlodipine Besylate and Hydrochlorothiazide in combine dosage form. Amlodipine Besylate (AML) is a long acting calcium channel blocker and in the treatment of CVS disorder. Hydrochlorothiazide (HCT) is a diuretic and antihypertensive. The mobile phase used was a combination of Water: Methanol (70:30). The detection of the combined dosage form was carried out at 245nm and a flow rate em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A literature survey revealed that many analytical methods have been reported for the determination of hydrochlorothiazide in pharmaceutical dosage forms and in biological samples using HPLC [3][4][5][6][7][8][9] , HPTLC 10 and spectrophotometry [11][12][13][14] techniques.…”
Section: Figure 1: Chemical Structure Of Hydrochlorothiazidementioning
confidence: 99%
“…A literature survey revealed that many analytical methods have been reported for the determination of hydrochlorothiazide in pharmaceutical dosage forms and in biological samples using HPLC [3][4][5][6][7][8][9] , HPTLC 10 and spectrophotometry [11][12][13][14] techniques.…”
Section: Figure 1: Chemical Structure Of Hydrochlorothiazidementioning
confidence: 99%
“…Literature survey revealed that Amlodipine besylate and Hydrochlorothiazide are official in the British Pharmacopoeia [14], Valsartan, Hydrochlorothiazide, and their mixture are official in the United States Pharmacopoeia [15]. There are reported methods for the determination of AML, VAL, or HCT in different dosage forms [2,4,[16][17][18][19] and in their binary mixtures [20][21][22]. Few methods were reported for the simultaneous estimation of AML, VAL, and HCT in their ternary mixture [23][24][25][26] and only one spectrophotometric method was developed for the determination of this mixture [27].…”
Section: Introductionmentioning
confidence: 99%
“…BEN and HCT are official in the british Pharmacopeia and the Indian Pharmacopeia. Many methods have been reported in the literature for both determination of BEN, individually and with other drugs in combination [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, there is no UV spectrophotometric method reported for the simultaneous estimation of BEN and HCT in pharmaceutical preparations in the literature survey.…”
Section: Introductionmentioning
confidence: 99%